2019
DOI: 10.1111/vde.12793
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of short‐course prednisolone during the initial phase of an elimination diet trial in dogs with food‐induced atopic dermatitis

Abstract: Background -Food allergy is a possible cause of atopic dermatitis (AD) in dogs; it is typically diagnosed following an eight-week elimination diet trial (EDT) and a provocation with the original diet. This lengthy procedure is difficult for owners and its interpretation may be unclear.Hypothesis/Objectives -To test the effect of prednisolone used in the first weeks of an EDT in order to reduce the total time period for diagnosis. The goal was to perform food challenges earlier than after the traditionally reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 17 publications
5
23
1
Order By: Relevance
“…The positive predictive value of the diagnostic tool "one or less than one relapse" to diagnose FIAD was 100% in all groups and the negative predictive value was 95% when using prednisolone, compared to 63% positive and 100% negative predictive values when using oclacitinib. Therefore, as already discussed herein and expected by Favrot et al, 7,11 prednisolone seems to be the better option for most dogs, probably as a consequence of the more rapid and broader anti-inflammatory effects of glucocorticoids. 7 Second, we wanted to assess the influence of the initial treatment duration.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…The positive predictive value of the diagnostic tool "one or less than one relapse" to diagnose FIAD was 100% in all groups and the negative predictive value was 95% when using prednisolone, compared to 63% positive and 100% negative predictive values when using oclacitinib. Therefore, as already discussed herein and expected by Favrot et al, 7,11 prednisolone seems to be the better option for most dogs, probably as a consequence of the more rapid and broader anti-inflammatory effects of glucocorticoids. 7 Second, we wanted to assess the influence of the initial treatment duration.…”
Section: Discussionsupporting
confidence: 69%
“…One explanation for the need of such a long period was a self‐perpetuating inflammatory process, which had to be overcome by long‐term elimination of allergen exposure 6 . A recent study showed that EDT duration could be successfully reduced by adding a short course of prednisolone in the initial EDT phase to switch off as many inflammatory pathways as possible, as soon as possible 7 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations